Deviations from the law of one price in Japan - Yin-Wong Cheung; Eiji Fujii (Center for Economic Studies and ifo Institute (CESifo), 2008)
Using 25 years of monthly data on individual Japanese retail prices, we study the behavior of product-specific Law of One Price (LOP) deviations. Individual tradable products, compared with nontradables, are more likely to have different distributions of LOP deviations across cities. Their distributions are also more likely to change over time. Individual LOP deviation series are found to display considerable persistence and there is limited evidence that tradability enhances price convergence. In addition, deviations from the LOP are found to display nonlinear trends, and these trends are not linearly related to a product's tradability. For individual products, LOP deviations are affected by their own inflation rates and, to a lesser extent, by aggregate inflation, output variations, and monetary variability. Interestingly, the trend behavior remains significant in the presence of these economic variables.
Keywords: F31; F34; F36; 330; price dispersion; tradability; asymmetric inflation effects; market integration; Einzelhandelspreisindex; Preisspanne; Internationaler Preiszusammenhang; Inflation; Handelbares Gut; Marktintegration; Japan